HYGIENIC ASSESSMENT OF JOINT ACTION OF DEFICIENCY OF IODINE AND FLUORIC POLLUTION ON THE CONDITION OF THE THYROID GLAND IN CHILDREN - N. S. Shin; M. F. Savchenkov; O. M. Zhurba; E. L. Goreva (Acta Biomedica Scientifica, 2013)
The content of fluorine in atmospheric air, in soil, and in system of centralized household-drinking water supply of city of Bratsk are studied, data of branch of Federal Budgetary Healthcare Institution «The Center of Hygiene and Epidemiology of Irkutsk Region» in Bratsk and region of Bratsk, data of Bratsk branch of state institution «Irkutsk CGMS - P» are used. The assessment of prevalence of iodine deficiency of children in two ecologically various districts of city of Bratsk is given. Results of obtained data are turned into practical recommendations on prevention of iodine deficiency in conditions of industrial influence of fluorine. In chosen areas examination of children of preschool age is provided. The number of surveyed made 98 persons including 49 girls and 49 boys. Iodine and fluorine excretion with urine, and also content of fluorine in teeth were defined. Iodine in urine was determined with a spectrophotocolorimetry method. The content of fluorine in urine was determined by an electrometric method with the use of fluoride selective electrode complete with pH in meter according to TORMENTS 4.1.773 - 99. Approved, certified methods of definition of fluorine in teeth do not exist in Russian Federation. Fluorine definition in teeth is based on reaction with alizarin complexon and cerium nitrate with formation of the painted connection. Now it is the only reaction used for direct photometric definition of fluorine. We came to conclusion that contents of fluorine in such biosubstrates as urine and teeth in children of the Central district, though doesn>t exceed admissible level, is significantly above the one of children living in settlement Energetic. This results from the fact that atmospheric air in the Central district is more polluted by fluoric connections. It is known that iodine and fluorine are halogens, and the second one possesses more expressed biological activity and can replace the first in the competitive way. Thus, in this research we tried to prove experimentally that urinary iodine indicators directly depend on industrial influence of fluorine.